Pemberdayaan Kelompok Wanita Tani melalui Program Agroeduwisata Melon Organik Kalibening (Agromelka) di Lampung Timur - Hening Hening; Agus Sutanto; Nani Septiana; Mia Cholvistaria cholvis; Beny Saputra (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2026)
Kalibening Village, East Lampung, is dominated by the agricultural sector with a monotonous rice and corn planting pattern that leads to decreased soil fertility, pest escalation, and dependence on chemical inputs. The majority of the harvest is sold to middlemen at low prices, and 234 families are categorized as poor families. Women Farmers Groups (KWT), which constitute 49% of the population, have potential but are hampered by a lack of knowledge and skills in organic cultivation, post-harvest processing, and digital marketing. The Agromelka Community Service Program (PkM) aims to empower KWT through training in organic melon and vegetable cultivation, the production of patented organic fertilizer (Pumakkal), diversification of processed products (organic pecel, ice cream, nuggets, juice), and digital-based agro-edu-tourism management. Implementation methods include socialization, training, intensive mentoring, and the application of technology (Venturi Injectors, IoT, screenhouses). As a result, there has been an increase in KWT capacity in production and marketing management, as evidenced by the ability to make processed products, packaging, branding, and manage educational gardens. This program contributes to SDGs 3 (Healthy Life) and 12 (Responsible Consumption and Production), as well as supporting the university's KPI